Penerapan Extreme Programming dalam Pengembangan Fitur Interoperabilitas Pada Aplikasi Bioinformatika - Edrian Hadinata; Tantri Hidayati Sinaga (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Extreme Programming or XP Model is an application development framework used to create applications that require rapid adaptation. Even in the condition that the application is still in use, the use of this development model is quite appropriate if it is applied to the development of Several features of Bioinformatics Applications. The widespread use of interoperability features found in many applications has made it easier for many system developers to develop applications on various system devices. Likewise, bioinformatics applications that carry out various in silico studies. Application development using the XP Model for special applications that are rarely used for feature additions, the difficulty is implementing rapid adaptation to interoperability feature development without design and analysis of specific applications. The contribution of this paper is to make notes and blueprints for adding interoperability features for bioinformatics applications. Besides that, the XP model is a different method when used to carry out the application development process, especially if it is used to add features to special applications. The success obtained in the development of this application cannot be separated from the advantages of the XP model itself, because the XP model can be implemented in conditions of lack of human resources and the possibility of applying practical principles and techniques in the process. As a result, development is carried out quickly and the application runs well through testing results and then applications can be used to perform processes in silico through interaction between applications to applications to the dataset provider.